Recurrent laryngeal nerve monitoring during thyroidectomy and parathyroidectomy in children. (April 2020) - Legré, M.; Bois, E.; Bernard, S.; Teissier, N.; Van Den Abbeele, T.
Abstract: Objective: Injury of the recurrent laryngeal nerve (RLN) is the most frequent complication of thyroid and parathyroid (TP) surgery. Monitoring of the RLN in children is not widely studied as this is not a common disease in the pediatric population. The aim of our study was to evaluate the reliability, feasibility and benefits of RLN monitoring during TP surgery in children. Methods: We analyzed all children who underwent TP surgery in our department between January 2009 and March 2018. Patients were classified into three groups: without monitoring (group 1), monitoring with an endotracheal tube (group 2) and monitoring with a double-needle electrode placed through the cricothyroid ligament (group 3). Results: We performed 53 surgeries (77 RLNs at risk) on 47 patients aged between 6 months and 18 years. Fourteen RLNs were in group 1, 47 in group 2 and 16 in group 3. We found one transient lesion of the RLN in group 1, three in group 2 and two in group 3. Seven patients in group 3 could not undergo monitoring with the tube because they need an orotracheal tube smaller than the smallest monitoring tube size available. The sensitivity and specificity values of the monitoring methods were 33% and 97% in group 2 and 67% and 100% in group 3, respectively. The positive and negative predictive values were 50% and 95% in group 2 and 100% and 92% in group 3, respectively. No complications arose during insertion of the electrode through the cricothyroid ligament. Conclusion: Monitoring of the RLN with a double-needle electrode inserted through the cricothyroid ligament is a reliable method with no associated complication, which is achievable at any age.